2014
DOI: 10.1177/0145445513518421
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Mobile Intervention to Improve Treatment Adherence in Bipolar Disorder

Abstract: We evaluated the feasibility and acceptability of a two week-long ecological momentary intervention (EMI), delivered via personal digital assistants (PDAs), to improve treatment adherence in bipolar disorder. EMIs use mobile technology to deliver treatment as clients engage in their typical daily routines, in their usual settings. Overall, participants (N = 14) stated that EMI sessions were helpful, user-friendly, and engaging, and reported satisfaction with the timing and burden of sessions, as well as the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(133 citation statements)
references
References 50 publications
6
121
1
5
Order By: Relevance
“…These patterns mirror those of studies of mobile interventions for other chronic conditions, which included study periods of up to a year in duration [53,55,58]. Despite generally high rates of adherence for this type of intervention, there appears to be considerable variation in usage of the different intervention components within and between studies, such as the self-care advice pages.…”
Section: Findings In the Context Of Other Literaturementioning
confidence: 55%
See 1 more Smart Citation
“…These patterns mirror those of studies of mobile interventions for other chronic conditions, which included study periods of up to a year in duration [53,55,58]. Despite generally high rates of adherence for this type of intervention, there appears to be considerable variation in usage of the different intervention components within and between studies, such as the self-care advice pages.…”
Section: Findings In the Context Of Other Literaturementioning
confidence: 55%
“…Additionally, very few barriers were reported by patients included in studies in the present review. The finding that few technical problems were experienced is in contrast to previous literature, where many patients have cited technical difficulties as a barrier to use and satisfaction with the intervention [52,54,57,58]. For example, one review of mobile interventions for patients with diabetes reported that 67% of 21 studies reported technical issues [54] and some patients have found these types of issues frustrating and dissatisfying [52].…”
Section: Findings In the Context Of Other Literaturementioning
confidence: 57%
“…Our study app was simple in its design: users can log, review, and visualize their mood. This simplicity ensures study results will generalize to the wealth of mobile and wearable technology developed for BP [12][13][14][15][16][17][18][19], translating into better technology for individuals with BP to monitoring symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, BP symptoms are being monitored passively through sensors on smartphones and wearable devices [12][13][14][15][16][17]. Smart-phone platforms MONARCA (MONitoring, treAtment and pRediCtion of bipolAr Disorder Episodes) [18] and PRIORI (Predicting Individual Outcomes for Rapid Intervention) [19] predict mood from patterns of speech and behavior from recorded calls, number of phone calls, and phone call duration.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in applying digital technologies to psychiatric practice has been increasing since the early 2000s, and recommendations for future research in this area were issued in 2013 by a technical expert panel convened by the Agency for Healthcare Research and Quality and the National Institute of Mental Health [10][11][12]. Examples of interventions that have used DHTs in patients with SMI include ecological momentary assessment and treatment interventions [13], computerized psychotherapies [14], cognitive remediation [15,16], family psychoeducation interventions [17], and interventions specifically targeting medication adherence [18].…”
Section: The Potential Of Digital Health Tools For Psychiatric Practicementioning
confidence: 99%